Motivasi Pemuda Bekerja di Sektor Pertanian di Kecamatan Gedong Tataan Kabupaten Pesawaran: Motivation of Youth to Work in the Agricultural Sector in the District of Gedong Tataan Pesawaran Regency - Bagus Denta Permana; Indah Listiana; Helvi Yanfika; Indah Nurmayasari (Journal of Agriculture and Social Development, 2023)
ABSTRACT Motivation is an impulse that arises in a person consciously or unconsciously to carry out an action with a specific purpose. This study aims to determine the level of youth motivation to work in the agricultural sector and the factors related to youth motivation to work in the agricultural sector and this research was conducted in Gedong Tataan District. The research method used was a survey method with a population of 100 young farmers. Based on the total population of young farmers, the total sample size was determined using the Frank Lynch formula (Sugiarto, 2003), so that a total sample of 43 respondents was obtained. The results showed that the level of motivation of young farmers in working in the agricultural sector in Bernung Village and Taman Sari was in the high category, this was evidenced by the fulfillment of physiological needs, safety needs, social needs, esteem needs and self-actualization needs. Factors related to the motivation of young farmers to work in the agricultural sector are land area variable (X2), land ownership status variable (X3), experience variable (X5) and assistance variable (X6). Factors that are not related to the motivation of young farmers to work in the agricultural sector include education variables (X1), distance to residence (X4) and non-formal education variables (X7). ABSTRAK   Motivation is an impulse that arises in a person consciously or unconsciously to carry out an action with a specific purpose. This study aims to determine the level of youth motivation to work in the agricultural sector and the factors related to youth motivation to work in the agricultural sector and this research was conducted in Gedong Tataan District. The research method used was a survey method with a population of 100 young farmers. Based on the total population of young farmers, the total sample size was determined using the Frank Lynch formula, so that a total sample of 43 respondents was obtained. The results showed that the level of motivation of young farmers in working in the agricultural sector in Bernung Village and Taman Sari was in the high category, this was evidenced by the fulfillment of physiological needs, safety needs, social needs, esteem needs and self-actualization needs. Factors related to the motivation of young farmers to work in the agricultural sector are land area variable (X2), land ownership status variable (X3), experience variable (X5) and assistance variable (X6). Factors that are not related to the motivation of young farmers to work in the agricultural sector include education variables (X1), distance to residence (X4) and non-formal education variables (X7).